Apologia osoby ludzkiej w nauczaniu Benedykta XVI - Warzeszak, Józef (Warszawskie Studia Teologiczne, 2023)
The author shows the teaching of Benedict XVI about the human person as its one great apologia. This apologia was about the primacy of God in all areas of human life, and thus it was also an apologia for man as a human person created in the image of God. How did the Pope seek to defend the human person? First of all, he considered every human person to be a specific center of social life, since each person, in one’s spiritual and moral dimension, is the source and goal of all human activity. Therefore, he had appealed for the promotion of a culture of respect for each such person, i.e. treating a rich person on an equal footing with an unborn, poor, starving, persecuted, economically exploited, without access to knowledge, in a word, everyone humiliated by unethical and harmful practices. He also recognized that the defense of the human person is also the defense of the common good, and vice versa. What was he protecting the person from? Against modern ideologies: biological reductionism, relativism, badly understood ecology. How did he protect it? First of all by showing its origin, greatness as well as inalienable dignity and vocation of the human person.